A metáfora nova de Nelson Rodrigues - Matheus Espíndola Ferreira (2017)
The present research tried, fundamentally, to study the new metaphors present in Nelson Rodrigues chronicles, with the objective of unveiling patterns for their composition, as well as for their use, and to elaborate a proposal on the way in which the construction of new metaphors contributes to the characterization of Nelson Rodrigues work. To achieve this purpose, a methodology was developed and applied to identify metaphors from electronic corpora based on collocates. Using the methodology of Corpus Linguistics, I proceeded to verify which of the metaphors present throughout the corpus were actually created by Nelson Rodrigues. Based on theories of cognitive semantics, the linguistic metaphors found were mapped into conceptual metaphors. The selected expressions were also analyzed having as theoretical apparatus the following theoretical areas: Prototypes Model, Mental Spaces and Blending Theory. Finally, it was investigated in available corpora whether metaphors created by Nelson Rodrigues were later employed in other discourses.